DIFFICULTIES IN THE RADIODIAGNOSIS OF LUNG INJURIES IN PHTHISIATRIC PRACTICE - R. B. Amansakhedov; A. V. Perfil’ev; A. E. Ergeshov; A. T. Sigaev (Вестник рентгенологии и радиологии, 2016)
The paper describes clinical cases of concomitant lung and intrathoracic lymph node involvements as evidenced by conventional radiography and computed tomography (CT). It shows difficulties in the differential diagnosis of different nosological entities in pulmonary tuberculosis. The x-ray semiotics of concomitant lung injuries is also depicted.